The dependence of reliability and mechanical strength of the solder joints in 3D PoP structures from sizes of solder powders applied in soldering materials. Issue 1 (6th February 2017) - Sitek, Janusz; Koscielski, Marek; Borecki, Janusz; Serzysko, Tomasz
Abstract : Purpose: The purpose of this paper is to evaluate the influence of solder powders sizes applied in soldering materials used for Package-on-Package (PoP) system manufacture as well as other factors on reliability and mechanical strength of created solder joints in three-dimensional (3D) PoP structures. Design/methodology/approach: The design of experiments based on the Genichi Taguchi method were used in the investigation. The main factors covered different printed circuit board (PCB) coatings, soldering materials with solder powders sizes from Types 3 to 7 and soldering profiles. The reliability of 3D PoP structures was determined by measurements of resistance of daisy-chain solder joints systems during thermal shocks (TS) cycles. The mechanical strength of solder joints in 3D PoP structures was determined by measurements of a shear force of "Top" layer of 3D structures at T0 and after 1, 500 TS. The ANOVA was used for results assessment. Findings: The size of solder powders applied in soldering materials had small (10 per cent) influence on mechanical strength of solder joints in 3D PoP structures. Small size of solder powder had positive effect on solder joints reliability in 3D PoP structures. Especially important was the selection of solder paste for "Bottom" layer of 3D PoP system (influence 17 per cent). Incorrect soldering profile (influence 46 per cent) or wrong selected PCB coating (influence 35 per cent) can very easily reduce the positive impact of soldering materials on solder joints reliability. It was stated that as low as possible soldering profile and organic solderability preservative (OSP) coating in the case of single-sided PCB are the best for 3D PoP structures due to their reliability. Originality/value: This paper explains how different sizes of solder powders used nowadays in solder pastes influence on reliability and mechanical strength of the solder joints in 3D PoP structures. The contribution, in numerical values, of soldering materials, soldering profile and PCB coating on 3D PoP structures solder joints reliability as well as recommendations improving reliability of 3D PoP structures solder joints were presented.